2018
DOI: 10.1002/ange.201712729
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Hydride Transfer in a Biological System: Insights into the Reaction Mechanism of the Light‐Dependent Protochlorophyllide Oxidoreductase

Abstract: Hydride transfer plays acrucial role in awide range of biological systems.H owever,i ts mode of action (concerted or stepwise) is still under debate.L ight-dependent NADPH: protochlorophyllide oxidoreductase (POR) catalyzest he stereospecific trans addition of ah ydride anion and ap roton across the C 17 À C 18 double bond of protochlorophyllide.T imeresolved absorption and emission spectroscopyw ere used to investigate the hydride transfer mechanism in POR. Apart from excited states of protochlorophyllide,t h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 33 publications
2
41
1
Order By: Relevance
“…As a specialized SDR, LPOR catalyzes the light-dependent reduction of Pchlide. Its catalytic mechanism has been investigated on the micro-to picosecond timescales (1,16,24,26,33,35,47). The process can be briefly described as: The photoactivated Pchlide receives a hydride from the electron donor NADPH at C17 of the C17 = C18 double bond, then a proton is transferred through a conserved tyrosine (Tyr193 in SyLPOR and TeLPOR) to C18, resulting in two chiral centers at C17 and C18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a specialized SDR, LPOR catalyzes the light-dependent reduction of Pchlide. Its catalytic mechanism has been investigated on the micro-to picosecond timescales (1,16,24,26,33,35,47). The process can be briefly described as: The photoactivated Pchlide receives a hydride from the electron donor NADPH at C17 of the C17 = C18 double bond, then a proton is transferred through a conserved tyrosine (Tyr193 in SyLPOR and TeLPOR) to C18, resulting in two chiral centers at C17 and C18.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive biochemical and biophysical studies have been performed on LPOR from two cyanobacteria, S. sp. PCC 6803 (18)(19)(20)(21)(22)(23)(24)(25)(26) and T. elongatus (27)(28)(29)(30)(31)(32)(33)(34)(35). The catalytic process has been demonstrated to be initiated by the absorption of light.…”
mentioning
confidence: 99%
“…Nature has discovered two completely different ways to achieve this reduction: in one, a lightdependent reaction is catalyzed by NADPH:protochlorophyllide oxidoreductase (LPOR; EC 1.3.1.33) (207,208); in the other, reduction of the C17-C18 double bond is catalyzed by a dark-operative protochlorophyllide reductase (DPOR), consisting of ChlL, ChlN and ChlB subunits that display similarity to the components of nitrogenase (209). The ability to trigger the catalytic cycle with short pulses of light has led to a number of kinetic studies (210)(211)(212), and recently the structure of LPOR has been reported (208). The phylogenetic distribution of LPOR and DPOR is interesting; anoxygenic photosynthetic bacteria contain only DPOR; cyanobacteria, green algae, mosses and most gymnosperms possess both LPOR and DPOR; and angiosperms (flowering plants) contain only LPOR.…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 99%
“…Pchlide excited-state electron transfer from NADPH followed by a proton-coupled electron transfer, 18 which represents the first example of the stepwise transfer of a hydride equivalent reported in biology. These time-resolved studies have provided insight into the chemistry of catalysis across a wide range of timescales (from the femtosecond to the second), but the required structural basis of POR photocatalysis has remained unknown.…”
mentioning
confidence: 99%
“…10,24,26 These excited-state interactions between Pchlide and POR stabilize a highly polarized C-17-C-18 double bond and enables stepwise hydride transfer from NADPH to C-17. 18 The polarized nature of the C-17-C-18 bond may also be stabilized by the close proximity of the hydroxyl group of Tyr193, which is known to be required for Pchlide photochemistry. 10 By contrast, Tyr223 does not form any direct interaction with Pchlide (Extended Data Fig.…”
mentioning
confidence: 99%